Virtual Reality Instructional Design in Orthopedic Physical Therapy Education: A Mixed-Methods Usability Test. (April 2022) - Hartstein, Aaron J.; Verkuyl, Margaret; Zimney, Kory; Yockey, Jean; Berg-Poppe, Patti
Background: Physical therapy education benefits from innovative and authentic learning opportunities. However, factors that influence the acceptance of educational technology must be assessed prior to curricular adoption. The purpose of this study was to assess the perceived ease of use and perceived usefulness of a virtual reality (VR) learning experience developed to promote the clinical decision-making of student physical therapists. Methods: A VR learning experience was developed, and an established two-stage usability test assessed player experience as well as the user's perception of both ease of use and usefulness. Two experts evaluated the VR learning experience and provided feedback. Six student physical therapists and five faculty members completed the VR experience, responded to two questionnaires, and participated in a semi-structured interview to further assess ease of use and utility. Results: High levels of perceived ease of use, perceived usefulness, and positive player experiences were reported by both faculty and student users. Faculty users perceived a significantly greater amount of educational and clinical utility from the VR simulation than did student users. Semi-structured interviews revealed themes related to ease of use, benefits, modeling of professional behaviors, and realism. Conclusion: Quantitative data supported faculty and student users' perceptions of ease of use, utility towards learning, practical application, and several constructs related to user experience. Qualitative data provided recommendations to modify design features of the VR experience. This study provides a template to design, produce, and assess the usability of an immersive VR learning experience that may be replicated by other health professions educators where current evidence is limited.